IMPLEMENTASI AKUNTANSI SEWA ASET SEBELUM DAN SESUDAH PENERAPAN PSAK 73 PADA LAPORAN KEUANGAN PT AS: IMPLEMENTASI AKUNTANSI SEWA ASET SEBELUM DAN SESUDAH PENERAPAN PSAK 73 PADA LAPORAN KEUANGAN PT AS - Asfufi Nanang (Accounting Journal of Ibrahimy (AJI), 2025)
This study examines the impact of the implementation of asset lease accounting before and after the enactment of PSAK 73 on the financial statements of PT AS. The research method uses a qualitative method with interview and observation data collection techniques. The results showed that PT AS before applying PSAK 73, the company applied PSAK 73 to replace PSAK 30 where for leased assets by recognising compressor and vehicle assets as operating leases so as to recognise rental expenses for each payment at the end of the period. After the company applies PSAK 73, the company recognises the lease of the two assets as a finance lease where the company will recognise right-of-use assets and lease liabilities on the statement of financial position and recognise amortisation expense at the end of the period. Implementation is inflicted on the financial statements before and after the implementation of PSAK 73 to make capitalisation of assets and record a reclassification journal for these change.